2016
DOI: 10.1007/s12630-016-0626-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and comparative costs of preoperative assessments for cataract surgery: traditional mandatory assessment versus a novel graded assessment system

Abstract: The graded system resulted in no major complications and a low rate of minor complications. The information obtained from the mandatory assessment is unlikely to prevent complications. Additionally, the cost effectiveness of the mandatory system was poor. This novel graded preoperative assessment system for cataract surgery patients can save time and resources by eliminating unnecessary patient visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Specifically, we identified no increase in the rates of intraoperative complications, noneyerelated ED visits, or inpatient readmissions after the intervention. These results are in line with several previous cataract surgery studies: Benoit et al 7 found no increase in adverse medical events with the omission of a preoperative history and physical examination for low-risk patients screened with a preoperative questionnaire; Alboim et al 8 and Jastrzebski et al 9 found no increase in adverse perioperative or postoperative outcomes and concluded that a comprehensive preoperative evaluation was minimally beneficial and not cost effective. The findings of our study strengthen the evidence for a tailored approach to cataract surgery preoperative evaluation to eliminate low-value interventions without compromising patient safety.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, we identified no increase in the rates of intraoperative complications, noneyerelated ED visits, or inpatient readmissions after the intervention. These results are in line with several previous cataract surgery studies: Benoit et al 7 found no increase in adverse medical events with the omission of a preoperative history and physical examination for low-risk patients screened with a preoperative questionnaire; Alboim et al 8 and Jastrzebski et al 9 found no increase in adverse perioperative or postoperative outcomes and concluded that a comprehensive preoperative evaluation was minimally beneficial and not cost effective. The findings of our study strengthen the evidence for a tailored approach to cataract surgery preoperative evaluation to eliminate low-value interventions without compromising patient safety.…”
Section: Discussionsupporting
confidence: 90%
“…3 Jastrzebski et al also advocates a graded approach to preoperative assessments. 4 Based on our results, we believe the universal application of independent and complete in-person H&Ps for patients undergoing cataract surgery is not medically necessary for most patients, represents low-value care, and increases visit burden. At BMC phone visits are now standard for all eye surgery, including non-cataract eye procedures, and is considering expansion of phone visits to other non-ocular procedures that are similarly short in duration requiring monitored IV sedation.…”
Section: Discussionmentioning
confidence: 68%
“…CEA are evaluated for surgical techniques; however, costs of clinical systems of cataract grading and preoperative new measurements have also been investigated. The high costs of setting up the novel technology are offset by low running costs [71,72]. In fact, other preoperative screening CEA cost-effectiveness analysis, CUA cost-utility analysis, ISCS immediate sequential cataract surgery, DSCS delayed sequential cataract surgery, VA visual acuity, ICER incremental cost-effectiveness ratio, QALY quality-adjusted life year measurements have been evaluated, such as optical coherence tomography (OCT) during the evaluation of a patient considering cataract surgery, being cost-effective from a third-party payer and societal perspective, as it could increase the detection of macular pathologies and improved the QALYs over time [74].…”
Section: Discussionmentioning
confidence: 99%